1974
DOI: 10.1136/bmj.2.5913.250
|View full text |Cite
|
Sign up to set email alerts
|

Response to Rimiterol and Salbutamol Aerosols Administered by Intermittent Positive-pressure Ventilation

Abstract: SummaryThe bronchodilator and cardiac effects produced by aerosols of 0G5% salbutamol and 0(5% and 1% rimiterol administered for three minutes in 40% oxygen by intermittent positivepressure ventilation (I.P.P.V.) were compared in 15 asthmatic patients. Salbutamol and both the concentrations of rimiterol were equipotent in peak bronchodilator effect, but salbutamol had a significantly longer duration of bronchodilator action. There was significantly less increase in heart rate after rimiterol than after salbuta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1975
1975
1989
1989

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Muscular tremor is a commonly reported, undesirable effect of oral 12-adrenoceptor stimulating drugs (Kennedy & Simpson, 1969;Freedman, 1971; Legge et al, 1971;Schumann & Herxheimer, 1971), however, few quantitative determinations have been made. Cooke et al (1974) also reported the frequent occurrence of tremor after salbutamol given by intermittent positive-pressure ventilation. By both these routes, higher plasma levels of the drugs are achieved initially, than when given by pressurized aerosol and are responsible for such effects (Walker, Evans, Richards & Paterson, 1972;.…”
Section: Digital Tremor Studiesmentioning
confidence: 93%
See 2 more Smart Citations
“…Muscular tremor is a commonly reported, undesirable effect of oral 12-adrenoceptor stimulating drugs (Kennedy & Simpson, 1969;Freedman, 1971; Legge et al, 1971;Schumann & Herxheimer, 1971), however, few quantitative determinations have been made. Cooke et al (1974) also reported the frequent occurrence of tremor after salbutamol given by intermittent positive-pressure ventilation. By both these routes, higher plasma levels of the drugs are achieved initially, than when given by pressurized aerosol and are responsible for such effects (Walker, Evans, Richards & Paterson, 1972;.…”
Section: Digital Tremor Studiesmentioning
confidence: 93%
“…In normal subjects the 12-selectivity of rimiterol by aerosol has been confirmed (Griffin & Turner, 1971;Phillips et al, 1971). Cooke et al (1974) recently compared salbutamol and rimiterol in equipotent bronchodilating doses by intermittent positive-pressure ventilation in asthmatic and normal subjects, and found that salbutamol produced greater and more prolonged tachycardia.…”
Section: Cardiovascular Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus both rimiterol and orciprenaline showed bronchodilator selectivity when used as aerosols in children, even though orciprenaline has been shown to be less,f2-selective than rimiterol in pharmacological studies (O'Donnell & Wanstall, 1974 Grant & Crompton, 1974) or in inhalation therapy using, for example, a Wright's nebulizer, the short duration of action of rimiterol may be an additional safety factor in that, if it should be necessary to withdraw therapy, the effects of the drug would be more readily reversed. A similar situation would apply to the use of this drug by the intravenous route.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in man have demonstrated rimiterol to be an effective short-acting bronchodilator by the inhalational and parenteral routes of administration, with a high degree of 12 -adrenoceptor selectivity (Griffin & Turner, 1971; Prime, Kamburoff & Gunthner, 1971; Phillips, Woolnough, Marinova & Turner, 1972; Svedmyr, Malmberg & Thiringer, 1972;Griffin, Williams & Maughan, 1973; Shenfield & Paterson, 1973;Cooke, Kerr, Willey, Hoare, Grant & Crompton, 1974;Evans, Shenfield, Thomas, Walker & Paterson, 1974;Bianco, Kamburoff & Prime, 1975; Marlin & Turner, 1975a, b & c Figure 1. The % FEV1 increases from control after all the doses of the drugs were significantly greater than those after placebo (P < 0.01).…”
mentioning
confidence: 99%